Trajectories of Age-Related Cognitive Decline and Potential Associated Factors of Cognitive Function in Senior Citizens of Beijing - Li, He; Lv, Chenlong; Zhang, Ting; Chen, Kewei; Chen, Chuansheng; Gai, Guozhong; Hu, Liangping; Wang, Yongyan; Zhang, Zhanjun (Current Alzheimer Research, 2014)
With a longer life expectancy and an increased prevalence of neurodegenerative diseases, investigations on trajectories of cognitive aging have become exciting and promising. This study aimed to estimate the patterns of age-related cognitive decline and the potential associated factors of cognitive function in community-dwelling residents of Beijing, China. In this study, 1248 older adults aged 52-88 years [including 175 mild cognitive impairment (MCI) subjects] completed a battery of neuropsychological scales. The personal information, including demographic information, medical history, eating habits, lifestyle regularity and leisure activities, was also collected. All cognitive function exhibited an agerelated decline in normal volunteers. Piece-wise linear fitting results suggested that performance on the Auditory Verbal Learning Test remained stable until 58 years of age and continued to decline thereafter. The decline in processing speed and executive function began during the early 50’s. Scores on visual-spatial and language tests declined after 66 years of age. The decline stage of the general mental status ranged from 63 to 70 years of age. However, the MCI group did not exhibit an obvious age-related decline in most cognitive tests. Multivariate linear regression analyses indicated that education, gender, leisure activities, diabetes and eating habits were associated with cognitive abilities. These results indicated various trajectories of age-related decline across multiple cognitive domains. We also found different patterns of agerelated cognitive decline between MCI and normal elderly. These findings could help improve the guidance of cognitive intervention program and have implications for public policy issues.
Keywords: mild cognitive impairment